2010
DOI: 10.1016/j.jchb.2010.01.048
|View full text |Cite
|
Sign up to set email alerts
|

A geometric morphometric study into the sexual dimorphism of the human scapula

Abstract: Sex determination is vital when attempting to establish identity from skeletal remains. Two methodological approaches to sex determination exist: morphological and metrical. The aim of this research paper was to use geometric morphometrics to study the shape of the scapula and its effect on the sexual dimorphism the scapula. The sample comprised of 45 adult black male and 45 adult black female scapulae of known individuals. The scapulae were photographed and 21 homologous landmarks were plotted to use for geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…[10] Y Scoltz found >91% accuracy for female and >95% accuracy for male in his study. [11] Ozer reported 82.9% -95% accuracy with highest accuracy for maximum scapular breadth. [12] Previous studies suggested that use of multiple variables give higher accuracy compared to the studies using single variable.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Y Scoltz found >91% accuracy for female and >95% accuracy for male in his study. [11] Ozer reported 82.9% -95% accuracy with highest accuracy for maximum scapular breadth. [12] Previous studies suggested that use of multiple variables give higher accuracy compared to the studies using single variable.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout life the scapular changes are not significant after development is finished [5,6], depending on these assumptions, researches already inspected the sexual diversity of the scapula in different populations [7]. With expanding interest for accurate sex determination; it is important to enhance variable estimation methods [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were done on determination of sex from scapula in different populations using either skeletal remains [1,3,[10][11][12][13][14][15], digital photographs [5,16] or multi -slice computed tomography (CT) [2,4,7,17,18] on different age groups and using different measurements. To the best of our insight, this Egyptian study is an interesting one which uses both scapulae in the determination of sex in Egyptians with different dimensions and different age group.…”
Section: Introductionmentioning
confidence: 99%
“…It allows for a detailed assessment of various aspects that may contribute towards differences in shape, and can also quantify the accuracies with which skeletons can be sorted into various groupings (e.g., sex) based on the observed shape differences. Two-and three-dimensional geometric morphometric assessments have been used to study sexual dimorphism in, for example, the skull (Rosas & Bastir, 2002;Bigoni et al, 2010), mandible (Oettlé et al, 2005;Franklin et al, 2007;Franklin et al, 2008), pelvis (Steyn et al, 2004;Gonzalez et al, 2009); and scapula (Scholtz et al, 2010). Kranioti et al (2009) also used geometric morphometrics to study shape differences in the proximal and distal ends of the humerus.…”
Section: Introductionmentioning
confidence: 99%